1869 Mich. Pub. Acts 157-58 - (:unkn) unknown (My University, 1869)
Second Regular Session, No. 247, § 15: [T]he common council shall have full power and authority to make by laws and ordinances . . . relative to keeping and sale of gunpowder, nitroglycerine, and all other dangerous and explosive articles, or burning fluids.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER